Efektivitas Metode Bermain (Menggunting dan Menempel) Terhadap Perkembangan Motorik Halus Anak - Oktavia Dwi Handayani; Mardiana (ABNA : Journal of Islamic Early Childhood Education, 2020)
This research is motivated by the existence of fine motor problems in children. The purpose of this study was to determine which method was more effective between the scissor play method or the sticky play method on children's fine motor development. This research is a type of quantitative research with an experimental approach with a post-test only design in August-October 2020. The data collection method used is a test. The population in this study were 73 children in group B at RAIT At-Taqwa Nguter Sukoharjo, the sample was 48 children. The sampling technique uses random sampling. The prerequisite test used the normality test and the homogeneity test. Data analysis using independent sample T test. The results of the analysis can be concluded that the scissor play method is more effective for children's fine motoric development compared to the sticky play method for group B children in RAIT At-Taqwa Nguter Sukoharjo for the 2020/2021 academic year. This is evidenced by the value of t count 4.025> t table value of 3.366. So that the proposed alternative hypothesis is accepted.